Three New Species of the Genus Scutiger (Amphibia: Anura: Megophryidae) from the Gaoligong Mountain Range in China, with An Updated Key to the Chinese Congeners - Wang, Kai; Yu, Zhongbin; Wu, Yunhe; Hou, Shao Bing; Wang, De; Xiong, Yun; Ye, Xin Long; Duan, Jian Ping; Li, Hai Jun; Li, Jie; Jin, Jie Qiong; Yang, Shen Pin; et al. (Zootaxa, 2025)
Lazy Toads of the genus Scutiger are a diverse group of alpine specialists in Asia. Despite continuous research on the taxonomy of the genus, the diversity is still underestimated. Integrating both molecular and morphometric analyses, we describe three new species of the genus Scutiger from the Gaoligong Mountain Range in Yunnan Province, China. Morphologically, these three species resemble S. gongshanensis, S. mammatus, and S. boulengeri, respetively, but they can be diagnosed from these recognized species and all other congeners by a suit of morphological characters, including the toe webbing status, numbers of pectoral glands and axillary glands with nuptial spines in breeding males, and the number of fingers covered with nuptial spines in breeding males. Additionally, they show considerable genetic divergences with respect to their morphologically similar species. We discussed the still underestimated diversity in Southwest China, the existing taxonomic problems of the genus, particularly regarding the validity and the whereabouts of type specimens of S. bangdaensis, S. biluoensis, and S. meiliensis, and we provide an updated key to all recognized species of China.